Thinking and Working Politically: from theory building to building an evidence base - Dasandi, Niheer; Marquette, Heather; Robinson, Mark (Research Paper, 2016)
This paper discusses the steps required to build a robust evidence base for 'thinking and working politically' (TWP) in development. It argues that better understanding what works, when and why is an important step in moving TWP into mainstream development programming. The paper reviews the existing evidence base on TWP, building on this and on other literature on public sector reform and 'pockets of effectiveness' to suggest research questions, case study selection criteria, and a four-level analytical framework: 1) political context; 2) sector; 3) organisation; and 4) individual. The framework aims to help build a 'rigorous enough' evidence base to show whether and how TWP happens and whether or not it influences the effectiveness of programme implementation and outcomes. The paper also calls for more focus on gender issues, and on different – and often more fragile – political contexts.
Keywords: IMPORTANT

What Does the Evidence Tell Us about ‘Thinking and Working Politically’ in Development Assistance? - Dasandi, Niheer; Laws, Ed; Marquette, Heather; Robinson, Mark (Politics and Governance, 2019)
Abstract: This paper critically reviews evidence on ‘thinking and working politically’ in development. Scholars and practitioners have increasingly recognised that development is fundamentally political, and efforts are underway to develop more politically informed ways of thinking and working. The literature does not yet constitute a strong evidence base to link these efforts to more effective aid programming: much evidence is anecdotal, does not meet high standards of robustness, is not comparative, and draws on self-selected successes reported by programme insiders. We discuss factors commonly considered to explain the success of politically informed programmes in areas where conventional programming approaches fall short. We consider evidence in three areas—political context, sector and organization—and provide guidance on where to focus next. Finally, we outline ways of testing the core assumptions of the ‘thinking and working politically’ agenda more thoroughly, to provide a clearer sense of the contribution it can make to aid effectiveness.